Chemical characterization of hemp seeds (Cannabis sativa L.) cultivated in the Ecuadorian Andes - Hugo Fernando Solís García; Luis Fernando Vargas Delgado; Andrés De la rosa-Martínez; Stalin Luis Fabrizzio Suntaxi Crisanto; Pablo Londoño-Larrea; David Gonzalez-Benitez; Carlos Montúfar-Delgado (CyTA - Journal of Food)
This research explored the influence of cultivating industrial hemp (Cannabis sativa L.) at an elevation of 2450 m AMSL in Ecuador on the composition and quality of seeds grown, particularly emphasizing their potential for food applications. Two extraction methods (Soxhlet and ultrasound-assisted extraction) were employed to analyze the oil’s fatty acid profile, while the solid residue’s protein, carbohydrate, and mineral content were also assessed. The predominant fatty acids identified were linoleic, linolenic, palmitic, and stearic acids. The Soxhlet method achieved the highest oil recovery, reaching 37.52% (w/w). Among the samples, the Ecuadorian variety “Latitud Cero” exhibited the highest protein content with a value of 26.75% (w/w). Microbiological and heavy metal analyses were performed to evaluate the safety for human consumption. This study provides valuable insights into the biochemical profile of hemp grown at high altitudes and contributes to improving food safety and quality in hemp seed production.